Long Term Plan for National Cancer Control Program in Indonesia - Subandoro, dr. Ratna R Suryo (Indonesian Journal of Cancer, 2009)
Cancer control program was known since 1989stated in Integrated & Comprehensive CancerControl Program(SK Menkes No 604/Menkes/SK/1989) Every hospital should develop their own cancercontrol program based on their resources & capacity(SK Menkes No 10/Menkes/SK/I/1994) n Indonesia participated in developing JakartaStatement on Cancer Control Program Ã¨ thestatement of strategic effort toward optimal cancercontrol and care (initiated by UICC & WHO) n Establishment of Dharmais Cancer Hospital (1993)in the future hopefully will become National CancerCenter n Establishment of Directorate of NCD Control,including Sub Directorate of Cancer ControlÂ Full text :http://www.scribd.com/doc/45477822